PENINGKATAN KETERAMPILAN MENAPIS DENGAN PAPAN TEKANG BAGI PENGRAJIN PEMULA DI DESA NEGERI KATON PROVINSI LAMPUNG - Noning Verawati; Soewito Soewito; Hanindyalaila Pienrasmi; Budhi Waskito; Ida Farida (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2022)
Abstract The decreased of local community’s ability in crafting pepadun tapis is a challenge in preserving the traditional cloth of Lampungnese as a local culture.The purpose of this training is to improve the skills of tapis beginner craftsmen using traditional tekang tools in Negeri Katon Village, Pesawaran District, Lampung Province. The training was carried out by involving 15 beginner craftsmen of pepadun tapis. The training stages are consist of three stages: preparation, implementation, and evaluation. The main materials and tools used in this training activity are gold thread, sewing thread, cloth, needle, scissors, and traditional tools called tekang board. The trainer of this event is a senior group leader of Tapis Jejama, craftsmen community in Negeri Katon Village.The result of this training shows that the beginner craftsmen are already has the basic skill of tapis pepadun crafting but still needs to be practiced more. The ability of designing pepadung tapis pattern and sewing skills are the basic skills that must be practiced regularly and intensively. The beginner craftsmen of pepadun tapis revealed that this training regenerated their awareness that crafting tapis is a local culture of Lampung that they have to upgrade their skills in using traditional tools tekang board.